PhD Education Challenges - Doctoral Candidatesâ€™ Perspectives - Nesterowicz, Krzysztof; Radicev, Slobodan; Fereshtehnejad, Seyed-Mohammad; Peacock, John; Nemeslaki, AndrÃ¡s (European Scientific Journal, ESJ, 2019)
Doctoral training was included in the Bologna system as the third cycle. The important consequence of this change is that the doctoral studies became more structured, and most universities now train doctors in a shorter time period than in the past, mostly in 3 to 4 years. The National Association of PhD students from Serbia (Doktoranti Srbije) conducted the same survey in the form of a questionnaire three years in a row (2010-2012). In 2010 the survey received 335 responses, in 2011 there were 557 responses and in 2012 there were 625. The survey results showed that doctoral candidates recognise supervision as a key issue that need to be improved. Surveyed individuals emphasised the impact of the supervisorâ€™s engagement on the quality of their PhD projects. Supportiveness is the quality that PhD students value the most. This involves supervisors being encouraging, and aware that students’ lives extend beyond the PhD. Other key areas for improvement, according to Serbian PhD candidates, are financing and mobility, especially international mobility.